Ascomycin and FK506: Pharmacology and Therapeutic Potential as Anticonvulsants and Neuroprotectants - Sierra‐Paredes, Germán (CNS Neurosci Ther, 2008)
Ascomycin and FK506 are powerful calcium‐dependent serine/threonine protein phosphatase (calcineurin [CaN], protein phosphatase 2B) inhibitors. Their mechanism of action involves the formation of a molecular complex with the intracellular FK506‐binding protein‐12 (FKBP12), thereby acquiring the ability to interact with CaN and to interfere with the dephosphorylation of various substrates. Pharmacological studies of ascomycin, FK506, and derivatives have mainly been focused on their action as immunosuppressants and therapeutic use in inflammatory skin diseases, both in animal studies and in humans. CaN inhibitors have been also proposed for the treatment of inflammatory and degenerative brain diseases. Preclinical studies suggest, however, that ascomycin and its derivatives exhibit additional pharmacological activities. Ascomycin has been shown to have anticonvulsant activity when perfused into the rat hippocampus via microdialysis probes, and ascomycin derivatives may be useful in preventing ischemic brain damage and neuronal death. Their pharmacological action in the brain may involve CaN‐mediated regulation of gamma aminobutyric acid (GABA) and glutamate receptor channels, neuronal cytoskeleton and dendritic spine morphology, as well as of the inflammatory responses in glial cells. FK506 and ascomycin inhibit signaling pathways in astrocytes and change the pattern of cytokine and neurotrophin gene expression. However, brain‐specific mechanisms of action other than CaN inhibition cannot be excluded. CaN is a likely potential target molecule in the treatment of central nervous system (CNS) diseases, so that the therapeutic potential of ascomycin, FK506, and nonimmunosuppressant ascomycin derivatives as CNS drugs should be further explored.